Investigating the antimicrobial and anti-adhesion properties of the alcoholic extract of Verbascum sinuatum plant on the biofilm formation of three intestinal bacteria. - Siahi, Fatemeh Seyed; Bonab, Zahra Hojjati (International Journal of Travel Medicine & Global Health, 2025)
Introduction: Intestinal bacteria enter the body through contaminated food and water or contact with infected people and animals. These bacteria cause blood, urine, bone or nervous system infections in humans. The most important bacteria that cause these diseases include Salmonella typhimurium, Klebsiella pneumoniae and Shigella sonnei. The increasing drug resistance of bacteria created the necessity of investigating the antibacterial effects of Verbascum sinuatum plant extract on the planktonic form and biofilm of all three bacteria in question. Methods: After preparing and cultivating standard bacteria and preparing biofilm from three intestinal bacteria, the effect of alcoholic extract of V.sinuatum on planktonic bacteria and the biofilm caused by them was investigated by well plate method. The value of minimum inhibitory concentration (MIC) and minimum bacteriocidal concenteration (MBC) was determined on planktonic form and biofilm of bacteria. Results: results showed that the alcoholic extract of V.sinuatum has antimicrobial effect on Salmonella typhimurium and Klebsiella pneumoniae. V.sinuatum also has inhibitory effect and has antimicrobial effect on the biofilm of Salmonella typhimurium and Klebsiella pneumoniae. Conclusion: The formation of biofilm is an important factor in stability and as a result, it is the cause of infections that are difficult to deal with. Klebsiella pneumoniae and Salmonella typhimurium also have the ability to form biofilm and it is considered an important cause of many infections, so it is important to fight this infectious factor using the extract of V.sinuatum plant.